Modelling of thin periodic plates subjected to large deflections = Modelowanie cienkich płyt periodycznych o dużych ugięciach - Domagalski, Łukasz; Jędrysiak, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objects under consideration are thin linear-elastic plates with periodic structure in planes parallel to the plate midplane, subjected to large (of the order of plate thickness) deflections. The main aim is to propose a mathematical model describing geometrically nonlinear problems of such plates, which is based on the tolerance averaging technique, cf. Woźniak et al. [3]. Results calculated for a special static problem by the tolerance model are compared with results obtained within the known tolerance linear model of thin plates.
Keywords: płyty periodyczne; zginanie nieliniowe; modelowanie tolerancyjne; periodic plates; nonlinear bending; tolerance modelling